Princípios terapêuticos e artísticos das artes marciais chinesas - de Oliveira Santos, Gilbert (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Chinese martial arts have a diverse range of principles that underpin their practice. Probably no other martial art present so powerfully aspects transiting in different dimensions of knowledge, through art, medicine, thought, spirituality and self-awareness. In this work, we will make a presentation of some artistic and therapeutic principles of this technique. These principles make it possible to deal with the challenge of marcialidade thought-provoking way, because moving the destructive power of martial gesture toward the beauty and preservation of psychophysical health.
Keywords: Chinese Martial Arts; Art; Health